Analysis of Student's Response toward The Types of Written Corrective Feedback Used by The English Teachers at SMAN I Tiumang - Widia Siska; Nidya Fitri (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the type of written correction used by the teacher in the writing of class XI students of SMAN 1 Tiumang, Dharmasraya Regency and student responses to feedback corrections. This type of research is qualitative. The data collection technique used is Cluster Random Sampling. Research instruments are documents and questionnaires. The sample taken in this study was students XI IPA 1, a total of 26 students. The document